(untitled) (International Journal of Engineering and Computer Science, 2014)
This study proposes a step-down tranformerless direct ac/dc converter suitable for universal line applications (90–270 Vrms ). The topology consists of a buck-type power-factor correction (PFC) cell with a buck–boost dc/dc cell and both works as a step down converter. A part of the input power is coupled to the output directly after the first power processing. With this direct power transfer feature and sharing capacitor voltages, the converter is able to achieve efficient power conversion, high power factor, low voltage stress on intermediate bus (less than 130 V) and low output voltage without a high step-down transformer. The absence of transformer reduces the component counts and cost of the converter. Both simulation and experimental results demonstrate the validity of the proposed converter.